Chromatic polymorphism in Trichomycterus jacupiranga from eastern Brazilian Coastal basins (Siluriformes: Trichomycteridae) - Vilardo, Paulo J.; Katz, Axel M.; Costa, Wilson J.e.m. (Zootaxa, 2023)
Trichomycterinae catfishes often have high intraspecific variability in colour patterns that may be associated with ontogenetic changes or habitat preferences. In species of the eastern South American genus Trichomycterus s.s., some cases of chromatic polymorphism have been reported but colour pattern is still considered an important tool for species identification. Herein, we first describe chromatic polymorphism in the geographically widespread T. jacupiranga, comparing populations from Tijuca National Park and Ribeira do Iguape basin, identifying four syntopic colour morphs. In addition, we performed a phylogenetic analysis using partial sequences of the mitochondrial gene 12Ss gene for 16 individuals of T. jacupiranga, with a maximum of 0.2% of genetic distance, corroborating T. jacupiranga as a single widespread species. Finally, based on our results and field observations, we concluded that it is not possible at the present to associate chromatic polymorphism in T. jacupiranga with habitat preferences, since specimens with different colouration in variable ontogenetic stages were found at the same microhabitats.